Megacities - Cambridge Educational (Firm). (Lawrenceville, NJ : Cambridge Educational, 2006)
This program travels to São Paulo, the world's third-largest megacity, to offer a glimpse of what it's like for the urban poor scraping out a living there. Visits to the slums and the streets of this 3,000-square-mile Brazilian metropolis paint a stark picture of a place where shootings, high levels of air and water pollution, and extreme traffic congestion continuously endanger the safety of its 18 million inhabitants.
DVD format.
Keywords: Sociology, Urban -- Brazil